Awareness of farmers regarding pesticides and their effects on health and environment: A cross-sectional study at Chisapani village - Jyoti, Sabita; Yadav, Mukesh; Yadav, Anika; Shah, Gaurav Jung; Bishwakarma , Prabin (International Journal of Occupational Safety and Health, 2026)
Introduction:  Over 66% of the population in Nepal is engaged in agriculture, where pesticide exposure is a common issue among farmer. The shortage of personal protective equipment (PPE) and inadequate education on proper PPE use and spraying techniques further increase the risk of pesticide exposure. As pesticides are essential for agriculture and public health, this study aims to assess farmers' awareness regarding pesticides and their effects on health and the environment.Methods: A cross-sectional study was conducted from 5th August to 5th November 2025 in Chisapani village of Baijanath Rural Municipality using convenience sampling. Ethical approval was obtained from the Institutional Review Committee. A total of 100 farmers who had been farming for more than 6 months were included in the study.Results: Among the respondents, 74% perceived pesticides as poison; however, more than half (51%) had used them for 5 to 10 years. The highest proportion, 45% used pesticides for growing both vegetables and grains and 95% sprayed two to three times per month. More than half (52%) do not use any personal protective equipment. Only 23% knew the correct use, 30% checked the expiry date and type and 22% followed the proper directions of use. Health effects were reported by 29%, and 20% reported chronic long-term effects. Respondents who agreed that pesticides affect the environment (the pesticides contaminate surface and groundwater and soil, air, and target and non-target vegetables) were 97 %.Conclusion: The study found a gap between awareness and safe pesticide-use practices among farmers. Most respondents recognize pesticides as poisonous but continue to use them for years, two to three times per month. Although farmers have experienced health issues, many continue to ignore them and still lack safe practices.